Analysis of the Use of Differentiated Instruction Learning Strategies in Answering Diverse Learning Needs in the Classroom of MAS Darul Hadist Hutabaringin Kec. Siabu Kab. Mandailing Natal - Aisah, Aisah (ALACRITY : Journal of Education, 2024)
This study aims to analyze the effectiveness of the use of Differentiated Instruction (DI) strategies in responding to diverse learning needs in the classroom of students at MAS Darul Hadist Hutabaringin Kec. Siabu Kab. Mandailing Natal. The research method used is a qualitative approach with data collection techniques through observation, interviews, and document analysis. The results of the study indicate that the implementation of DI can increase students' motivation, involvement, and understanding of the subject matter. Teachers apply grouping based on interests and abilities and vary learning methods to adjust to student characteristics, which contribute positively to their learning outcomes. The implementation of DI faces challenges in the form of limited time, resources, and learning facilities. Teachers need additional preparation to adapt materials and methods, and institutional support is needed so that the implementation of DI runs optimally. This study concludes that DI is an effective learning strategy in improving the quality of education in school environments with diverse learning needs, and recommends that schools support the implementation of DI through ongoing training and improving learning facilities.